RHETORICAL RHETORICAL STRATEGIES: THE ANALYSIS OF THE LETTER FROM SUNAK TO PRABOWO - Evi Saputra; Carla Maretha; Eryon (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
This study analyzes the rhetorical strategies in the letter of UK Prime Minister Rishi Sunak to Prabowo Subianto, the newly elected President of Indonesia, following the 2024 Indonesian Presidential Elections. The letter highlights the longstanding diplomatic relations between the UK and Indonesia as a formal communication to strengthen bilateral ties and foster future collaboration. Sunak effectively conveys a message of goodwill, strategic partnership, and cooperation through rhetorical devices, modes, and appeals. The research employs a qualitative content analysis method to examine the rhetorical elements in the letter, identifying how Sunak utilizes language to align with broader political goals. The study reveals the significance of political rhetoric in shaping international diplomacy, offering insights into the intricate communication strategies that underlie diplomatic correspondence.